Positive electrode active material, method for producing the same, and non-aqueous electrolyte secondary battery

JP2026165239APending Publication Date: 2026-10-14AICHI STEEL CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025057522
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0011】 前記正極活物質は、前記特定の組成式で現れる組成と、空間群P63mcに帰属可能なO2型層状構造を有する活物質粒子から構成されている。このように、活物質粒子中に微量のNbが含まれていることにより、個々の活物資粒子におけるc軸方向の長さを長くし、活物質粒子のアスペクト比Aを低くすることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026165239000001_ABST
    Figure 2026165239000001_ABST
Patent Text Reader

Abstract

The present invention provides a positive electrode active material that can easily reduce the internal resistance of a battery, a method for producing the same, and a non-aqueous electrolyte secondary battery. [Solution] The active material particles 10 constituting the positive electrode active material 1 have a composition represented by a specific composition formula and an O2-type layered structure that can be attributed to the space group P63mc. The Ferret diameter in the c-axis direction in the secondary electron image of each active material particle 10 is L C (Unit: μm) is used, and the Ferret diameter in the direction perpendicular to the c-axis is L A When expressed in units of μm, the standard deviation of aspect ratio A, represented by the following formula (1), is 0.6 or less. A=L A / L C ...(1)
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a positive electrode active material, a method for producing the same, and a non-aqueous electrolyte secondary battery.

Background Art

[0002] Non-aqueous electrolyte secondary batteries such as lithium ion secondary batteries have excellent characteristics such as being small and lightweight while having high electromotive force and high energy density. Taking advantage of these excellent characteristics, non-aqueous electrolyte secondary batteries are used in a wide range of applications including small electronic devices such as mobile phones and laptop computers, and large electric drive devices such as electric vehicles and hybrid vehicles.

[0003] As the positive electrode active material for non-aqueous electrolyte secondary batteries, Li 0.8 Mn 0.5 Co 0.5 A lithium oxide such as O2 may be used. This type of positive electrode active material is produced by preparing a Na-doped precursor composed of an oxide containing Na, and then replacing Na in the Na-doped precursor with Li through ion exchange.

[0004] For example, Patent Document 1 describes a method for producing a positive electrode active material, which includes a Na-doped precursor preparation step of preparing a sodium-containing transition metal oxide having a P2 structure belonging to the space group P63 / mmc, and an ion exchange step of replacing at least part of the sodium contained in the sodium-containing transition metal oxide with lithium by an ion exchange method, wherein at least lithium iodide is used as a Li ion source in the ion exchange step.

Prior Art Documents

Patent Documents

[0005]

Patent Document 1

Summary of the Invention

Problems to be Solved by the Invention

[0006] The crystal structure of the positive electrode active material obtained by the method described in Patent Document 1 is an O2-type layered structure. In addition, the Li migration path in the O2-type layered structure is formed along the c-plane of the crystal. Therefore, in the positive electrode active material having an O2-type layered structure, from the viewpoint of rapidly performing insertion of Li from the outside into the particles constituting the positive electrode active material and desorption of Li from the inside of the active material particles to the outside, it is desirable to increase the length of the active material particles in the c-axis direction and widen the area of the a-plane exposed on the surface of the active material particles and the crystallographically equivalent plane to the a-plane. However, since the active material particles having an O2-type layered structure tend to have a flat shape in which the length in the a-axis direction is longer than the length in the c-axis direction, it has been difficult to increase the length in the c-axis direction.

[0007] The present invention has been made in view of such a background, and aims to provide a positive electrode active material capable of easily reducing the internal resistance of a battery, a method for producing the same, and a non-aqueous electrolyte secondary battery. [Means for Solving the Problems]

[0008] One aspect of the present invention is a positive electrode active material for use in a non-aqueous electrolyte secondary battery, The active material particles constituting the positive electrode active material have a composition formula of Li a Na b Ni c Co d Mn e Nb f M g O2 (wherein a to g in the aforementioned composition formula satisfy the relationships of 0.6<a≦1.4, 0≦b≦0.2, 0.1<c<0.3, 0<d<0.65, 0.3<e<0.9, 0.005<f<0.1, 0≦g<0.2, and M is at least one additive element selected from the group consisting of B, Mg, Al, K, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Mo and W), and an O2-type layered structure that can be assigned to the space group P63mc, The Feret diameter in the c-axis direction in the secondary electron image of each of the aforementioned active material particles is defined as L C(Unit: μm), and the Feret diameter in the direction perpendicular to the c-axis is represented as L A (Unit: μm), the positive electrode active material has a standard deviation of the aspect ratio A represented by the following formula (1) of 0.6 or less. A=L A / L C ···(1)

[0009] Another aspect of the present invention resides in a non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte, wherein The positive electrode contains the positive electrode active material according to the above aspect.

[0010] Still another aspect of the present invention resides in a method for producing the positive electrode active material according to the above aspect, wherein A precursor containing two or more elements selected from the group consisting of Ni, Co, Mn, Nb and the additional element M is prepared, A mixture containing the precursor, a Na source, and a Nb source is fired in an oxidizing gas atmosphere, thereby obtaining Na b0 Ni c Co d Mn e Nb f M g A Na-doped precursor having a composition represented by the composition formula of O2 (wherein b0 to g in the composition formula satisfy the relationships 0.6<b0≦1.6, 0.1<c<0.3, 0<d<0.65, 0.3<e<0.9, 0.005<f<0.1, 0≦g<0.2, and M is at least one additional element selected from the group consisting of B, Mg, Al, K, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Mo and W) and a P2-type layered structure is prepared, The mixture of the Na-doped precursor and a Li source is heated, and Na in the Na-doped precursor is replaced with Li by ion exchange to produce the positive electrode active material. This is the method for producing the positive electrode active material. [Advantageous Effects of the Invention]

[0011] The positive electrode active material is composed of active material particles having a composition that appears in the specific composition formula and an O2-type layered structure that can be attributed to space group P63mc. In this way, the inclusion of a small amount of Nb in the active material particles increases the c-axis length of each active material particle and lowers the aspect ratio A of the active material particles.

[0012] Furthermore, the standard deviation of the aspect ratio A of the active material particles is within the specified range. In this way, by increasing the length in the c-axis direction of the positive electrode active material particles and further reducing the variation in the aspect ratio A of the active material particles, the proportion of active material particles with a large exposed area of ​​the a-plane and crystallographically equivalent planes can be increased. Therefore, a positive electrode active material consisting of such active material particles can easily reduce the internal resistance of the battery.

[0013] The positive electrode of the non-aqueous electrolyte secondary battery contains the positive electrode active material. Therefore, the internal resistance of the non-aqueous electrolyte secondary battery can be easily reduced.

[0014] In the method for producing the positive electrode active material, a Na-doped precursor is produced by calcining a mixture containing a precursor having the specific composition, a Na source, and an Nb source. By producing a Na-doped precursor in this way, particles with a low aspect ratio A can be obtained more easily. Then, by performing ion exchange using such a Na-doped precursor, the positive electrode active material can be easily obtained.

[0015] As described above, according to the above embodiment, it is possible to provide a positive electrode active material that can easily reduce the internal resistance of a battery, a method for manufacturing the same, and a non-aqueous electrolyte secondary battery. [Brief explanation of the drawing]

[0016] [Figure 1] Figure 1 is a schematic diagram of the secondary electron image of the active material particles constituting the positive electrode active material. [Figure 2]Figure 2 is an explanatory diagram showing X-ray diffraction patterns of Na-doped precursors a8, b2 and b3 in Example 1. [Figure 3] Figure 3 is an explanatory diagram showing a secondary electron image of Na-doped precursor a3 in Example 1. [Figure 4] Figure 4 is an explanatory diagram showing a secondary electron image of Na-doped precursor c1 in Example 1. [Figure 5] Figure 5 is an element mapping image showing the distribution of Nb in the active material particles in active material A3 of Example 1. [Mode for Carrying Out the Invention]

[0017] (Positive Electrode Active Material) [Composition] The active material particles constituting the positive electrode active material have a composition formula of Li a Na b Ni c Co d Mn e Nb f M g O2 (wherein a to g in the composition formula satisfy the relationships of 0.6<a≦1.4, 0≦b≦0.2, 0.1<c<0.3, 0<d<0.65, 0.3<e<0.9, 0.005<f<0.1, and 0≦g<0.2, and M is at least one additive element selected from the group consisting of B, Mg, Al, K, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Mo and W). The active material particles also have an O2-type layered structure assignable to space group P63mc.

[0018] The value of a in the above compositional formula, that is, the ratio of moles of lithium (Li) to moles of oxygen (O) when the number of moles of oxygen (O) is 2, is greater than 0.6 and less than or equal to 1.4. This makes it easy to improve the discharge capacity of the positive electrode. If the value of a in the above compositional formula is greater than 1.4, the stability of the O2-type layered structure decreases, and a crystalline phase having a crystalline structure other than the O2-type layered structure is more likely to form. As a result, it may become difficult to obtain active material particles having the desired crystalline phase. From the viewpoint of more reliably improving the stability of the O2-type layered structure, the value of a in the above compositional formula is preferably 1.35 or less, more preferably 1.3 or less, even more preferably 1.25 or less, and particularly preferably 1.2 or less.

[0019] Furthermore, if the value of a in the above compositional formula is 0.6 or less, the discharge capacity of the positive electrode may decrease. From the viewpoint of further improving the discharge capacity of the positive electrode, the value of a in the above compositional formula is preferably 0.7 or more, more preferably 0.8 or more, even more preferably 0.85 or more, even more preferably 0.9 or more, particularly preferably 0.95 or more, and most preferably 1.0 or more. In this case, a crystalline phase having an O2-type layered structure can be more easily formed in the active material particles.

[0020] In determining the preferred range for the value of a in the aforementioned compositional formula, the upper and lower limits of the value of a described above can be arbitrarily combined. For example, the preferred range for the value of a in the aforementioned compositional formula may be 0.7 or more and 1.4 or less, 0.8 or more and 1.35 or less, 0.85 or more and 1.3 or less, 0.9 or more and 1.25 or less, 0.95 or more and 1.20 or less, or 1.0 or more and 1.2 or less.

[0021] The positive electrode active material may contain Na (sodium) as an optional component. The value of b in the composition formula, that is, the ratio of moles of Na to moles of O when the number of moles of O is 2, should be between 0 and 0.2. Preferably, the value of b in the composition formula is between 0 and 0.15, more preferably between 0 and 0.1, and even more preferably between 0 and 0.05.

[0022] The values ​​of c and e in the above compositional formula are each within the specified range. By setting the content of Ni (nickel) and Mn (manganese) in the active material particles to each within the specified range, a crystalline phase having an O2-type layered structure can be formed more easily in the active material particles.

[0023] In the above compositional formula, the value of d, that is, the ratio of the number of moles of Co (cobalt) to the number of moles of O when the number of moles of O is 2, is greater than 0 and less than 0.65. By adding Co to the positive electrode active material, the chemical stability of the positive electrode active material can be increased, and the discharge capacity of the positive electrode can be easily improved. From the viewpoint of further improving the chemical stability of the positive electrode active material, the value of d in the above compositional formula is preferably 0.15 or more, more preferably 0.21 or more, even more preferably 0.27 or more, particularly preferably 0.32 or more, and most preferably 0.37 or more.

[0024] On the other hand, if the value of d in the above compositional formula is 0.65 or higher, the discharge capacity of the positive electrode may decrease. From the viewpoint of more easily avoiding a decrease in the discharge capacity of the positive electrode, the value of d in the above compositional formula is preferably 0.62 or less, more preferably 0.57 or less, even more preferably 0.52 or less, particularly preferably 0.47 or less, and most preferably 0.42 or less.

[0025] In determining the preferred range for the value of d in the aforementioned compositional formula, the upper and lower limits of the value of d described above can be arbitrarily combined. For example, the preferred range for the value of d in the aforementioned compositional formula may be 0.15 or more and 0.62 or less, 0.21 or more and 0.57 or less, 0.27 or more and 0.52 or less, 0.32 or more and 0.47 or less, or 0.37 or more and 0.42 or less.

[0026] The value of f in the above compositional formula, that is, the ratio of moles of Nb (niobium) to moles of O when the number of moles of O is 2, is greater than 0.005 and less than 0.1. By keeping the Nb content in the active material particles within the above specific range, the length of the c-axis direction of individual active material particles can be easily increased, and the aspect ratio A of the active material particles can be easily decreased. From the viewpoint of more reliably obtaining this effect, the value of f in the above compositional formula is preferably greater than 0.005 and less than 0.08, more preferably greater than 0.005 and less than 0.06, and even more preferably greater than 0.005 and less than 0.04.

[0027] The reason why Nb produces the aforementioned effects is not entirely clear at this time, but the following reasons are possible. Specifically, it is presumed that Nb has the effect of suppressing crystal growth in the a-axis direction or promoting crystal growth in the c-axis direction during the calcination of the Na-doped precursor. Therefore, by adding Nb, it is thought that the rate at which crystals grow in the a-axis direction becomes slower than the rate at which they grow in the c-axis direction during the calcination of the Na-doped precursor. As a result, it is thought that the c-axis length of individual active material particles can be easily increased, and the aspect ratio A of the active material particles can be easily lowered.

[0028] The positive electrode active material may contain, as an optional component, at least one additive element M selected from the group consisting of B (boron), Mg (magnesium), Al (aluminum), K (potassium), Ca (calcium), Ti (titanium), V (vanadium), Cr (chromium), Fe (iron), Cu (copper), Zn (zinc), Ga (gallium), Ge (germanium), Sr (strontium), Y (ytterbium), Zr (zirconium), Mo (molybdenum), and W (tungsten). The value of g in the composition formula, that is, the ratio of the number of moles of additive element M to the number of moles of O when the number of moles of O is 2, should be 0 or greater and less than 0.2.

[0029] From the viewpoint of more reliably forming a crystalline phase having an O2-type layered structure in the active material particles, the sum of the values ​​of c, d, e, f, and g in the above composition formula is preferably greater than 0.95 and less than 1.05, more preferably greater than 0.97 and less than 1.03, and even more preferably greater than 0.99 and less than 1.01.

[0030] [Crystal structure] The active material particles contain at least a crystalline phase having an O2-type layered structure. The active material may also contain a crystalline phase having a crystalline structure other than the O2-type layered structure, to the extent that it does not impair the effects described above. The content of the crystalline phase having a crystalline structure other than the O2-type layered structure is preferably 20% by mass or less, more preferably 15% by mass or less, and even more preferably 10% by mass or less.

[0031] Furthermore, the content of the crystalline phase in the active material particles, as described above, can be calculated based on the X-ray diffraction pattern obtained by powder X-ray diffraction. More specifically, the scanning range of the diffraction angle 2θ in powder X-ray diffraction is set to 10° to 90°, the scanning speed to 2° / min, the sampling width to 0.02°, and the X-ray source to be CuKα rays. By performing Rietveld analysis based on the X-ray diffraction pattern obtained under these measurement conditions, the type of crystalline phase in the active material particles can be identified and the content of each crystalline phase can be calculated.

[0032] [Shape of active material particles] The c-axis direction of the Ferret diameter in the secondary electron image of each of the active material particles is L. C (Unit: μm) is used, and the Ferret diameter in the direction perpendicular to the c-axis is L A When expressed in units of μm, the standard deviation of aspect ratio A, represented by the following formula (1), is 0.6 or less. A=L A / L C ...(1)

[0033] By setting the standard deviation of the aspect ratio A of the active material particles within the specified range, the proportion of active material particles with a long c-axis length in the positive electrode active material can be increased. Therefore, the positive electrode active material can easily reduce the internal resistance of the battery.

[0034] If the standard deviation of the aspect ratio A of the active material particles exceeds 0.6, the proportion of active material particles with a long c-axis length in the positive electrode active material tends to decrease. Therefore, this may lead to an increase in the internal resistance of the battery. From the viewpoint of reducing the internal resistance of the battery, there is no lower limit to the standard deviation of the aspect ratio A of the active material particles, but when the positive electrode active material is manufactured by the manufacturing method described later, the standard deviation of the aspect ratio A of the active material particles will be, for example, 0.2 or higher.

[0035] The arithmetic mean of the aspect ratio A of the active material particles is preferably between 0.8 and 1.5. In this case, the length of the active material particles in the c-axis direction can be increased. As a result, the internal resistance of the battery can be reduced more easily.

[0036] The method for calculating the aspect ratio A, its arithmetic mean, and standard deviation of the active material particles is as follows. First, the powdered positive electrode active material is observed using a secondary electron microscope, and secondary electron images of the active material particles are taken. Figure 1 schematically shows the secondary electron images of the active material particles 10 that constitute the positive electrode active material 1.

[0037] As shown in Figure 1, among the end faces of the active material particle 10, the end face 101 where the c-plane of the O2-type layered structure is exposed has a uniform contrast. On the other hand, among the end faces of the active material particle 10, the end face 102 where the plane parallel to the c-axis of the O2-type layered structure is exposed shows a striped pattern originating from the layered structure. Therefore, by observing the direction of the striped pattern appearing on the end face 102 in the secondary electron image of the active material particle 10, the orientation of the c-axis of each individual active material particle 10 can be determined. More specifically, the orientation of the c-axis of the active material particle 10 is parallel to the stacking direction of the layered structure, that is, the direction in which the contrast of the striped pattern appearing on the end face 102 changes alternately.

[0038] Next, from the active material particles 10 that appear in the secondary electron image, active material particles 10a that have a roughly rectangular outline and only the striped end faces 102 are observed are extracted as the target for calculating the aspect ratio A. Then, for the extracted active material particles 10a, the rectangle with the smallest area among the rectangles that circumscribe the active material particles 10a is set. The length of the side in this rectangle that is roughly parallel to the c-axis is the length L in the c-axis direction. C (Unit: μm) The length of the side approximately perpendicular to the c-axis is defined as the Ferret diameter L in the direction perpendicular to the c-axis. A (Unit: μm) And the Ferret diameter L in the direction perpendicular to the c-axis. A (Unit: μm) Ferret diameter L in the c-axis direction C The aspect ratio A of each active material particle is calculated by dividing by (unit: μm).

[0039] By taking the arithmetic mean of the aspect ratio A obtained above, the arithmetic mean of the aspect ratio of the active material particles can be calculated. Furthermore, the standard deviation A of the aspect ratio of the active material particles can also be calculated. SD This is the aspect ratio of each active material particle obtained above and the arithmetic mean A of the aspect ratios. ave Using these, it is calculated by the following formula (2).

[0040]

number

[0041] In addition, in equation (2) above, n is the total number of active material particles for which the aspect ratio has been calculated, and A i is the aspect ratio of the i-th active material particle. The number of active material particles used to calculate the standard deviation and arithmetic mean of aspect ratio A is not particularly limited, but by using the aspect ratios of 100 or more active material particles, for example, a standard deviation and arithmetic mean of aspect ratio A closer to the true value can be obtained. If there are not enough active material particles in a single secondary electron image, multiple secondary electron images may be taken, and the standard deviation and arithmetic mean of aspect ratio A may be calculated based on the active material particles contained therein.

[0042] The active material particles have a surface layer covering their outermost surface, and it is preferable that the Nb concentration of the surface layer is higher than the average Nb concentration contained in the active material particles. In this case, the length of the active material particles in the c-axis direction tends to be longer. Therefore, a positive electrode active material consisting of such active material particles tends to have a higher proportion of active material particles with a long c-axis direction, making it easier to reduce the internal resistance of the battery.

[0043] The positive electrode active material is usually used in powder form from the viewpoint of shortening the diffusion distance of lithium ions within the positive electrode active material. The positive electrode active material has a median diameter (i.e., D) in its volume-based particle size distribution. 50 It is preferable that the positive electrode active material is composed of particles with a median diameter of 10 μm or less. That is, the positive electrode active material may be, for example, a powder having a particle size distribution such that the median diameter is 10 μm or less, or an aggregate of primary particles with a median diameter of 10 μm or less. In this case, the diffusion distance of lithium ions in the positive electrode active material can be shortened, and the internal resistance in the non-aqueous electrolyte secondary battery can be reduced more easily. From the viewpoint of shortening the diffusion distance of lithium ions in the positive electrode active material, it is preferable that the positive electrode active material is composed of primary particles with a median diameter of 1 μm or less.

[0044] Furthermore, the particle size of the positive electrode active material can be determined using a laser diffraction / scattering particle size distribution analyzer (for example, "Partica® LA-960V2" manufactured by Horiba, Ltd.). In addition, the median diameter of the Na-doped precursor is defined as the particle size at which the cumulative value of the frequency of the smallest particles in the volume-based particle size distribution obtained using the laser diffraction / scattering particle size distribution analyzer reaches 50% (i.e., the 50% cumulative particle size).

[0045] [Court layer] The positive electrode active material is made of a material that conducts Li ions and may have a coating layer covering at least a portion of the surface of the positive electrode active material. By providing a coating layer on the surface of the positive electrode active material, it is possible to ensure a conduction path for Li ions while suppressing direct contact between the positive electrode active material and other materials constituting the positive electrode.

[0046] The coating layer may be composed of inorganic or organic materials. Furthermore, the materials constituting the coating layer may be doped with elements such as Li. From the viewpoint of more easily improving the Li ion conductivity of the coating layer, it is preferable that the coating layer be composed of inorganic materials. Examples of inorganic materials constituting the coating layer include oxide solid electrolytes such as Li-containing oxides and Li-containing oxynitrides. From the viewpoint of more easily improving the resistance of the positive electrode active material, it is more preferable that the coating layer is an oxide containing Li, B, P, and O. In addition to Li-containing oxides, the coating layer may also contain inorganic materials other than Li-containing oxides, such as Li-containing halides.

[0047] (Method for manufacturing positive electrode active material) The positive electrode active material is prepared by creating a precursor containing, for example, two or more elements selected from the group consisting of Ni, Co, Mn, Nb, and the aforementioned additive element M. By calcining a mixture containing the aforementioned precursor, a Na source, and a Nb source in an oxidizing gas atmosphere, Na b0 Ni c Co d Mn e Nb f M ga compositional formula of O2 (wherein b0 to g in the aforementioned compositional formula satisfy the relationships 0.6<b0≦1.6, 0.1<c<0.3, 0<d<0.65, 0.3<e<0.9, 0.005<f<0.1, and 0≦g<0.2, and M is at least one additive element selected from the group consisting of B, Mg, Al, K, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Mo and W), and a P2-type layered structure is produced, It is obtained by heating a mixture of the Na-doped precursor and a Li source, and substituting Na in the Na-doped precursor with Li through ion exchange.

[0048] [Production of Precursor] As a method for producing the precursor, for example, a coprecipitation method can be adopted. By producing the precursor via the coprecipitation method, the uneven distribution of elements inside the precursor can be further reduced. Furthermore, by producing the precursor via the coprecipitation method, the effect of suppressing crystal growth in the a-axis direction when producing the Na-doped precursor can be more reliably obtained.

[0049] When producing the precursor by the coprecipitation method, first, a first raw material solution containing two or more ions selected from Ni ions, Co ions, Mn ions, Nb ions, and ions of the additive element M, and an alkaline second raw material solution are prepared. The first raw material solution can be produced, for example, by dissolving nitrates, sulfates, hydroxides, carbonates and the like of the aforementioned metal elements in water. The concentration of each ion in the first raw material solution may be appropriately set according to the desired composition in the positive electrode active material. As the second raw material solution, for example, an aqueous solution of a base such as sodium carbonate or sodium hydroxide can be used.

[0050] Next, the first raw material solution and the second raw material solution are mixed. This forms a precursor containing the aforementioned metal element in the mixture of the first and second raw material solutions. When mixing the first and second raw material solutions, a complex-forming agent can be added to the mixture as needed to adjust the rate of precipitate formation. Examples of complex-forming agents include aqueous ammonia and aqueous trisodium citrate.

[0051] [Preparation of Na-doped precursors] Next, a mixture containing the precursor obtained in this manner, a Na source, and an Nb source is calcined in an oxidizing gas atmosphere to produce a Na-doped precursor having the specific composition and P2-type layered structure. As mentioned above, Nb is thought to have the effect of slowing the crystal growth rate in the a-axis direction during calcination compared to the crystal growth rate in the c-axis direction. Therefore, by adding a small amount of Nb to the mixture and calcining it, a Na-doped precursor containing many particles with a long c-axis length can be easily obtained. From the viewpoint of obtaining this effect more reliably, it is preferable that the ratio of Nb atoms to the total number of atoms of all metal elements in the mixture be 0.5 atomic% to 10 atomic%, and more preferably 0.5 atomic% to 8 atomic%.

[0052] Examples of compounds that can be used as a source of sodium include sodium carbonate, sodium oxide, sodium nitrate, and sodium hydroxide.

[0053] As the Nb source compound, it is preferable to use at least one Nb-containing compound selected from the group consisting of ammonium niobium oxalate, niobium ethoxide, niobium pentoxide, niobium hydroxide, and niobium pentachloride. In this case, crystal growth in the a-axis direction during calcination can be more effectively suppressed. As a result, the proportion of active material particles with a low aspect ratio contained in the positive electrode active material can be increased.

[0054] The compound that serves as the Nb source may be in powder form. In this case, the mixture can be obtained by mixing the Nb source together with the precursor and the Na source. Alternatively, the Nb source can be attached to the surface of the precursor by dissolving the compound that serves as the Nb source in a solvent and then spraying the Nb source solution onto the surface of the precursor.

[0055] Li sources, Ni sources, Mn sources, Co sources, and sources of additive element M may be added to the mixture as needed. For example, lithium carbonate can be used as a Li source compound.

[0056] The proportions of precursors and other elements in the mixture can be appropriately set according to the desired composition of the positive electrode active material. From the viewpoint of more easily adjusting the Nb content in the Na-doped precursor to within the specified range, it is preferable to blend the Nb source such that the ratio of Nb atoms to the total number of atoms of all metal elements in the mixture is 1.0 atomic% or more and 15 atomic% or less.

[0057] Next, the mixture is calcined under an oxidizing gas atmosphere to produce a Na-doped precursor having the composition represented by the specific composition formula and a P2-type layered structure. Since the Na-doped precursor after calcination is in the form of a lump, it is preferable to crush the calcined body after the calcination is complete. The method of crushing the calcined body is not particularly limited. For example, various methods can be used for crushing, such as manual crushing using a mortar and pestle or mechanical crushing using a ball mill. After crushing the precursor, the powder may be classified as needed to adjust the particle size of the Na-doped precursor.

[0058] As an oxidizing gas, for example, air can be used. If the firing temperature is too low, the P2-type layered structure will not be sufficiently formed in the Na-doped precursor. On the other hand, if the firing temperature is too high, a crystalline phase having a crystalline structure other than the P2-type layered structure is more likely to form in the Na-doped precursor.

[0059] From the viewpoint of more easily obtaining a Na-doped precursor having a P2-type layered structure, the calcination temperature during firing is preferably 700 to 1100°C, and more preferably 800 to 1000°C. In this case, a Na-doped precursor consisting solely of a P2-type layered structure can be obtained more easily. The holding time during firing can be appropriately set from the range of 0.5 to 48 hours.

[0060] The content of the crystalline phase having a P2-type layered structure in the Na-doped precursor is preferably 50% by mass or more, more preferably 85% by mass or more, even more preferably 90% by mass or more, particularly preferably 95% by mass or more, and most preferably 100% by mass, that is, the Na-doped precursor is composed solely of the crystalline phase having a P2-type layered structure. By increasing the content of the crystalline phase having a P2-type layered structure, the content of the crystalline phase having an O2-type layered structure in the final cathode active material can be easily increased.

[0061] The content of the P2-type layered structure in the aforementioned Na-doped precursor can be calculated, for example, based on the X-ray diffraction pattern obtained by powder X-ray diffraction.

[0062] [Ion exchange] After obtaining the Na-doped precursor as described above, the Na atoms in the Na-doped precursor are replaced with Li atoms by ion exchange. The specific method of ion exchange is not particularly limited, but for example, a method of heating the Na-doped precursor in contact with a Li ion source can be employed. In this case, lithium salts such as lithium chloride or lithium nitrate can be used as the Li ion source. The heating temperature during ion exchange should be such that the Li ion source melts.

[0063] When a mixture of lithium salts is used as the Li ion source, the heating temperature during ion exchange is preferably 400°C or lower. In this case, the formation of a crystalline phase having a crystalline structure other than the O2-type layered structure can be suppressed. From the viewpoint of further increasing the content of the O2-type layered structure in the positive electrode active material, the heating temperature during ion exchange is more preferably 350°C or lower. The heating time during ion exchange can be appropriately set from, for example, a range of 0.5 to 8 hours.

[0064] Furthermore, the Na atoms in the Na-doped precursor can be replaced with Li atoms by contacting the Na-doped precursor with an aqueous solution containing Li ions. In this case, the aqueous solution containing Li ions may be heated as needed to promote ion exchange. As the aqueous solution to be contacted with the Na-doped precursor, an aqueous solution of a lithium salt such as lithium chloride or lithium nitrate can be used. The concentration of Li ions in the aqueous solution can be appropriately set from, for example, a range of 1 to 10 mol%. The contact time between the Na-doped precursor and the aqueous solution can be appropriately set from, for example, a range of 10 to 300 hours.

[0065] The positive electrode active material can be obtained by substituting the Na ions in the Na-doped precursor with Li ions as described above. After ion exchange is complete, the obtained positive electrode active material may be crushed into a powder as needed. The method of crushing the calcined body is not particularly limited. For example, various methods can be used for crushing, such as manual crushing using a mortar and pestle or mechanical crushing using a ball mill. Furthermore, after crushing the calcined body, the powder may be classified as needed to adjust the particle size of the positive electrode active material.

[0066] [Formation of the coating layer] The above manufacturing method may include a step of forming a coating layer on the surface of the positive electrode active material. The method of forming the coating layer is not particularly limited, and an appropriate method can be selected from known methods depending on the material constituting the coating layer, the desired thickness of the coating layer, the area ratio of the coating layer on the surface of the positive electrode active material, etc.

[0067] For example, if the raw materials for the coating layer can be dissolved in a solvent, the coating layer can be formed by the following method. First, the raw materials for the coating layer are dissolved in a solvent to prepare a coating solution. This coating solution is then applied to the surface of the positive electrode active material. Subsequently, the coating solution applied to the surface of the positive electrode active material is dried to form a coating layer on the surface of the positive electrode active material. For example, spray drying can be used as a drying method for the coating solution.

[0068] [Li dope] The above manufacturing method may include a step of further doping the positive electrode active material with Li. The timing of the Li doping is not particularly limited as long as it is performed after ion exchange. For example, when a coating layer is formed on the surface of the positive electrode active material, the Li doping may be performed before forming the coating layer, or after forming the coating layer.

[0069] The method of doping with Li is not particularly limited, and known methods can be used as appropriate. For example, the positive electrode active material can be doped with Li by bringing a reducing solution containing Li ions into contact with the positive electrode active material.

[0070] (Nonaqueous electrolyte secondary battery) The positive electrode active material is configured to be used as the positive electrode in a non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte, with lithium ions as the charge carrier. The non-aqueous electrolyte in the non-aqueous electrolyte secondary battery using the positive electrode active material may be liquid or solid. That is, non-aqueous electrolyte secondary batteries to which the positive electrode active material can be applied include, for example, secondary batteries using a non-aqueous electrolyte such as lithium-ion secondary batteries, and all-solid-state secondary batteries using lithium ions as the charge carrier and a solid electrolyte.

[0071] A lithium-ion secondary battery may primarily consist of a positive electrode containing the positive electrode active material, a negative electrode, a separator interposed between the positive and negative electrodes, a non-aqueous electrolyte, additives, and a case housing these components. Examples of lithium-ion secondary battery shapes include coin-type, cylindrical, stacked, and prismatic types.

[0072] The positive electrode of a lithium-ion secondary battery comprises a positive electrode active material and a positive electrode current collector that holds the positive electrode active material. Various conductors can be used as the positive electrode current collector, such as metal foils like copper foil, stainless steel mesh, aluminum foil, and nickel foil, as well as perforated metal, expanded metal, and metal mesh.

[0073] The positive electrode may contain a binder interposed between the positive electrode active material and the positive electrode current collector. Examples of binders include fluorine-based binders such as polyvinylidene fluoride and polytetrafluoroethylene, rubber-based binders such as styrene-butadiene rubber, olefin-based binders such as polypropylene and polyethylene, and cellulose-based binders such as carboxymethylcellulose.

[0074] Furthermore, the positive electrode may contain conductive agents or conductive additives to enhance electrical conductivity. Examples of conductive agents include graphite, carbon black, acetylene black, and coke.

[0075] The positive electrode can be manufactured, for example, by the following method. First, a paste-like positive electrode mixture containing positive electrode active material is prepared. The positive electrode mixture may optionally contain an organic solvent to disperse or dissolve solid components such as the positive electrode active material. Next, the positive electrode mixture is applied to the surface of the positive electrode current collector and then dried to form a positive electrode active material layer on the surface of the positive electrode current collector. After forming the positive electrode active material layer, the positive electrode active material layer may be pressed to increase its density if necessary. The positive electrode can then be obtained.

[0076] The negative electrode of a lithium-ion secondary battery comprises a negative electrode active material and a negative electrode current collector that holds the negative electrode active material. Examples of negative electrode active materials include silicon-based active materials such as Si, Si alloys and silicon oxide, carbon materials having a graphite structure such as graphite and hard carbon, and lithium titanate (Li4Ti5O 12 Lithium oxides such as ) metallic lithium and lithium alloys can be used. In addition, the same conductor as the positive electrode current collector described above can be used as the negative electrode current collector.

[0077] The negative electrode, like the positive electrode, may contain a binder, a conductive agent, and a conductive additive. The binder, conductive agent, and conductive additive that can be used in the negative electrode are the same as those used in the positive electrode.

[0078] The method for manufacturing the negative electrode is the same as for the positive electrode. That is, first, a paste-like negative electrode mixture containing negative electrode active material is prepared. The negative electrode mixture may contain an organic solvent to disperse or dissolve solid components such as the negative electrode active material, if necessary. Next, the negative electrode mixture is applied to the surface of the negative electrode current collector and then dried to form a negative electrode active material layer on the surface of the negative electrode current collector. After forming the negative electrode active material layer, the negative electrode active material layer may be pressed to increase its density, if necessary. A negative electrode can be obtained by the above method.

[0079] The non-aqueous electrolyte may contain an organic solvent and an electrolyte consisting of a lithium salt. Examples of lithium salts include LiPF6. Examples of organic solvents include ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, monofluoroethylene carbonate, and methyl-2,2,2-trifluoroethyl carbonate. These organic solvents may be used individually or in combination of two or more.

[0080] The non-aqueous electrolyte preferably contains at least one organic solvent selected from ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate. These organic solvents are highly polar and can dissolve large amounts of electrolyte. Therefore, by preparing a non-aqueous electrolyte using these organic solvents, the transport fraction of the charge carrier in a lithium-ion secondary battery can be easily increased.

[0081] Furthermore, an all-solid-state secondary battery may include, for example, a positive electrode containing the positive electrode active material, a negative electrode containing the negative electrode active material, a separator interposed between the positive and negative electrodes and containing a solid electrolyte, and a case for housing these components as its main constituent elements.

[0082] The positive electrode of an all-solid-state secondary battery may be composed of, for example, a positive electrode active material, a solid electrolyte, and additives such as conductive agents, which may be added as needed. In this case, from the viewpoint of further increasing the energy density of the secondary battery, the content of the positive electrode active material in the positive electrode is preferably 60 to 99% by mass, and more preferably 70 to 95% by mass.

[0083] Examples of solid electrolytes used in the positive electrode of all-solid-state secondary batteries include lithium lanthanum zirconate, LiPON, and Li 1+X Al X Ge 2-X Oxide solid electrolytes such as (PO4)3, Li-SiO glass, and Li-Al-SO glass, or sulfide solid electrolytes such as Li2S-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Si2S-P2S5, Li2S-P2S5-LiI-LiBr, LiI-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, and Li2S-P2S5-GeS2 can be used. The solid electrolyte content in the positive electrode is preferably 1 to 40% by mass, and more preferably 5 to 30% by mass.

[0084] When a conductive agent and a conductive additive are added to the positive electrode, the content of the conductive agent and conductive additive can be appropriately set according to the electrical conductivity, ionic conductivity, and the desired energy density of the secondary battery. The additives used in the positive electrode of an all-solid-state secondary battery are the same as those used in the positive electrode of a lithium-ion secondary battery.

[0085] The negative electrode of an all-solid-state secondary battery may consist, for example, of a negative electrode active material, a solid electrolyte, and additives such as conductive agents added as needed. The negative electrode active material and additives used in the negative electrode of an all-solid-state secondary battery are the same as those used in the negative electrode of a lithium-ion secondary battery. Furthermore, the solid electrolyte used in the negative electrode is the same as the solid electrolyte used in the positive electrode as described above.

[0086] The separator of an all-solid-state secondary battery contains a solid electrolyte. The solid electrolyte used in the separator is the same as the solid electrolyte used in the positive electrode as described above. In addition to the solid electrolyte, the separator may contain a binder to bind the solid electrolyte particles together, if necessary. Examples of binders that can be used include fluororesins such as polyvinylidene fluoride, polytetrafluoroethylene, and fluororubber, and thermoplastic resins such as polypropylene, polyethylene, and polyethylene terephthalate. [Examples]

[0087] (Example 1) Examples of the positive electrode active material and its manufacturing method will be described with reference to Figures 2 to 5. The positive electrode active material in this example is used in a non-aqueous electrolyte secondary battery. The active material particles constituting the positive electrode active material are Li a Na b Ni c Co d Mn e Nb f M gThe composition is represented by the O2 compositional formula (where a to g in the aforementioned compositional formula satisfy the relationships 0.6<a≦1.4, 0≦b≦0.2, 0.1<c<0.3, 0<d<0.65, 0.3<e<0.9, 0.005<f<0.1, 0≦g<0.2, and M is at least one additive element selected from the group consisting of B, Mg, Al, K, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Mo and W), and has an O2-type layered structure assignable to the space group P63mc. The Feret diameter in the c-axis direction in the secondary electron image of each of the individual active material particles is defined as L C (unit: μm), and the Feret diameter in the direction perpendicular to the c-axis is defined as L A (unit: μm), the standard deviation of the aspect ratio A represented by the following formula (1) is 0.6 or less. A=L A / L C ···(1)

[0088] The positive electrode active material of the present example is produced by preparing a precursor containing two or more elements selected from the group consisting of Ni, Co, Mn, Nb and the aforementioned additive element M, and calcining a mixture containing the aforementioned precursor, a Na source, and a Nb source in an oxidizing gas atmosphere, thereby obtaining a composition represented by the compositional formula Na b0 Ni c Co d Mn e Nb f M g O2 (where b0 to g in the aforementioned compositional formula satisfy the relationships 0.6<b0≦1.6, 0.1<c<0.3, 0<d<0.65, 0.3<e<0.9, 0.005<f<0.1, 0≦g<0.2, and M is at least one additive element selected from the group consisting of B, Mg, Al, K, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Mo and W), and a Na-doped precursor having a P2-type layered structure is fabricated, and then heating a mixture of the aforementioned Na-doped precursor and a Li source to replace Na in the Na-doped precursor with Li through ion exchange. A more specific method for producing the positive electrode active material of the present example is described below.

[0089] [Preparation of precursors] Precursors P1 to P6, shown in Table 1, were prepared by coprecipitation.

[0090] • Precursors P1, P2 Nickel sulfate hexahydrate as the Ni source, cobalt sulfate heptahydrate as the Co source, and manganese sulfate pentahydrate as the Mn source were weighed out so that the molar ratios of Mn, Ni, and Co atoms were as shown in Table 1. These compounds were then dissolved in distilled water to a metal atom concentration of 2 mol / L to prepare the first raw material solution. Sodium hydroxide was dissolved in distilled water to a concentration of 25 w / v% to prepare the second raw material solution. Furthermore, ammonia water and distilled water were mixed to a complex-forming agent with an ammonia concentration of 1 mol / L. Separately from these solutions, distilled water was prepared in a beaker as the reaction solution.

[0091] Next, while stirring the reaction solution, the first raw material solution, the second raw material solution, and the complexing agent were simultaneously added dropwise to the reaction solution, and Ni, Co, and Mn were coprecipitated in the beaker to obtain a precursor consisting of hydroxide salts of these metal elements. At this time, the dropping rate of the second raw material solution was adjusted so that the pH of the reaction solution was 10.5. The temperature of the reaction solution during dropping was kept within the range of 30 to 40°C, and the time required from the start of dropping to the end of the reaction was within the range of 1 to 8.5 hours.

[0092] After the reaction was complete, the precursor in the beaker was filtered and washed with distilled water. The washed coprecipitation precursor was heated at 100°C for 12 hours to dry it, and then crushed using an agate mortar to obtain powdered precursors P1 and P2.

[0093] • Precursors P3, P4 Nickel sulfate hexahydrate as the Ni source, cobalt sulfate heptahydrate as the Co source, and manganese sulfate pentahydrate as the Mn source were weighed out so that the molar ratios of Mn, Ni, and Co atoms were as shown in Table 1. These compounds were then dissolved in distilled water to a concentration of 2 mol / L to prepare the first raw material solution. Sodium carbonate was also dissolved in distilled water to a concentration of 2 mol / L to prepare the second raw material solution. Separately from these solutions, a 0.1 mol / L trisodium citrate aqueous solution was prepared in a beaker as the reaction solution.

[0094] Next, the first and second raw material solutions were simultaneously added dropwise to the reaction solution while stirring, and Ni, Co, and Mn were coprecipitated in the beaker to obtain a precursor consisting of carbonates of these metal elements. At this time, the dropping rate of the second raw material solution was adjusted so that the pH of the reaction solution was 7.3. The temperature of the reaction solution during dropping was kept within the range of 30 to 50°C, and the time required from the start of dropping to the end of the reaction was within the range of 1 to 6 hours.

[0095] After the reaction was complete, the precursor in the beaker was filtered and washed with distilled water. The washed coprecipitation precursor was heated at 100°C for 12 hours to dry it, and then crushed using an agate mortar to obtain powdered precursors P3 and P4.

[0096] • Precursors P5, P6 The method for preparing precursors P5 and P6 is generally the same as that for preparing precursors P3 and P4, except that ammonium niobium oxalate is added as an Nb source to the first raw material solution.

[0097] Table 1 shows the composition of precursors P1 to P6 and the median diameter in the volume-based particle size distribution. A laser diffraction / scattering particle size distribution analyzer (Partica® LA-960V2, manufactured by Horiba, Ltd.) was used to measure the volume-based particle size distribution of precursors P1 to P6.

[0098] [Table 1]

[0099] [Preparation of positive electrode active material] ·Active material A1~A6, B1 A mixture was prepared by mixing precursor P1 with sodium carbonate as a Na source and ammonium niobium oxalate as a Nb source. The amount of Nb source added was set so that the atomic ratio of Nb to all metal elements in the mixture was as shown in Table 2. This mixture was heated in air at 600°C for 6 hours, and then calcined at 910°C for 2 hours to obtain a Na-doped precursor. The obtained Na-doped precursor was crushed using an agate mortar and pestle to obtain a powder.

[0100] Table 2 shows the molar ratios of each metal element in the Na-doped precursor when the molar ratio of oxygen atoms is set to 2. The molar ratios of the Na-doped precursor were measured by inductively coupled plasma emission spectrometry (i.e., ICP-AES).

[0101] Furthermore, the crystal structure of the Na-doped precursor was identified by powder X-ray diffraction. A Rigaku Corporation "SmartLab®" X-ray diffractometer was used, and the characteristic X-ray irradiated was the CuKα line. The scanning range for the diffraction angle 2θ was 10° to 90°, the scanning speed was 2° / min, and the sampling width was 0.02°. As an example, Figure 2 shows the X-ray diffraction pattern of Na-doped precursor a3 used in the preparation of active material A3. All Na-doped precursors used in the preparation of active materials A1 to A6 were composed of a crystalline phase with a P2-type layered structure.

[0102] The median diameter in the volume-based particle size distribution of the Na-doped precursor was as shown in Table 2. A laser diffraction / scattering particle size distribution analyzer (Partica® LA-960V2, manufactured by Horiba, Ltd.) was used to measure the volume-based particle size distribution of the Na-doped precursor.

[0103] Table 2 shows the arithmetic mean and standard deviation of the aspect ratios of the Na-doped precursors calculated based on secondary electron images. The method for calculating the arithmetic mean and standard deviation of the aspect ratios of the Na-doped precursors is the same as the method for calculating the arithmetic mean and standard deviation of aspect ratio A in the positive electrode active material described above, except that the Na-doped precursor is used instead of the positive electrode active material. As an example, Figure 3 shows the secondary electron image of the Na-doped precursor a3 used in the preparation of active material A3. Also, Figure 4 shows the secondary electron image of the Na-doped precursor c1 used in the preparation of active material C1, which will be described later.

[0104] Next, a Li source containing lithium nitrate and lithium chloride in a molar ratio of 1:1 was prepared. This Li source and a Na-doped precursor were mixed so that the number of moles of Li was 10 times the number of moles of Na to prepare a mixture. This mixture was heated in air at a temperature of 280°C for 1 hour to perform ion exchange and obtain a lump of positive electrode active material. After the ion exchange was completed, the positive electrode active material was washed with pure water. Then, the lump of positive electrode active material was crushed using a mortar and pestle to obtain powdered positive electrode active material (active materials A1-A6, B1).

[0105] Table 3 shows the molar ratios of each metal element in active materials A1 and A3, assuming a molar ratio of 2 for oxygen atoms. The composition of the active materials was measured by ICP-AES.

[0106] ·Active materials A7~A8, B2~B3 The method for preparing these active materials is the same as that for preparing active material A3, except that the maximum temperature during calcination of the Na-doped precursor was changed from 910°C to the temperatures shown in Table 3. Furthermore, according to the X-ray diffraction patterns shown in Figure 2, the Na-doped precursor b2 used to prepare active material B2 and the Na-doped precursor b3 used to prepare active material B3 contained both a crystalline phase with a P2-type layered structure and a crystalline phase with a P3-type layered structure.

[0107] ·Active material A9~A10 The method for preparing these active materials is the same as the method for preparing active material A4, except that the precursors shown in Table 3 were used instead of precursor P1.

[0108] ·Active material A11 The method for preparing active material A11 is the same as that for preparing active material A3, except that precursor P4 was used instead of precursor P1.

[0109] ·Active material B4~B5 The method for preparing these active materials is the same as the method for preparing active material B1, except that the precursors shown in Table 3 were used instead of precursor P1.

[0110] ·Active material C1~C3 The method for preparing these active materials is the same as the method for preparing active materials A1, A9, or A10, except that an Nb source was not added when calcining the Na-doped precursor.

[0111] [Median diameter, arithmetic mean, and standard deviation of the aspect ratio of the positive electrode active material] When ion exchange is performed under the conditions described above, crystal growth of the positive electrode active material hardly occurs during ion exchange. Therefore, the median diameter, arithmetic mean and standard deviation of the aspect ratio of the positive electrode active material are the same as the median diameter, arithmetic mean and standard deviation of the aspect ratio of the Na-doped precursor shown in Table 2.

[0112] [Structure of active material particles] Figure 5 shows an Nb mapping image obtained by observing a cross-section of an active material particle 10 constituting active material A3 using a transmission electron microscope, and mapping the positions of Nb atoms. As shown in Figure 5, it can be seen that a surface layer 13, where Nb is concentrated, is formed on the outermost surface of the active material particle 10 constituting active material A3. The Nb concentration in the surface layer 13 was higher than the average concentration of Nb contained in the active material particle 10. Although not shown in the figure, it is presumed that, similar to active material A3, active materials A1-A2, A4-A11, and B1-B5, to which an Nb source was added during the preparation of the Na-doped precursor, also have a surface layer 13 formed on the outermost surface of the active material particle 10, similar to active material A3.

[0113] [Table 2]

[0114] As shown in Table 2, in the process of producing active materials A1 to A11, a Na-doped precursor having a composition within the specified range is produced by calcining a mixture containing a precursor, a Na source, and an Nb source. Therefore, the standard deviation of the aspect ratio of the Na-doped precursor used in the production of active materials A1 to A11 was 0.6 or less. Furthermore, as mentioned above, it is estimated that the standard deviation of the aspect ratio of the active material particles constituting the positive electrode active material is the same as the standard deviation of the aspect ratio of the Na-doped precursor, and therefore it is estimated that the standard deviation of the aspect ratio of the active material particles constituting active materials A1 to A11 falls within the specified range.

[0115] In contrast, the atomic ratio of Nb in the Na-doped precursors used to produce active materials B1, B4-B5 is lower than the specified range mentioned above. Therefore, the standard deviation of the aspect ratio of the Na-doped precursors used to produce these active materials was greater than 0.6. Consequently, it is estimated that the standard deviation of the aspect ratio of the active material particles constituting active materials B1, B4-B5 is greater than 0.6.

[0116] In the process of preparing the active material B2, the Na-doped precursor was calcined at a temperature lower than the specified range, making it impossible to obtain a Na-doped precursor with the desired crystal structure.

[0117] During the preparation of active material B3, the Na-doped precursor was calcined at a temperature higher than the specified range, making it impossible to obtain a Na-doped precursor with the desired crystal structure.

[0118] In the preparation process for active materials C1-C3, the Na-doped precursor was calcined without the addition of an Nb source. Therefore, the standard deviation of the aspect ratio of the Na-doped precursor was greater than 0.6. Consequently, it is estimated that the standard deviation of the aspect ratio of the active material particles constituting active materials C1-C3 is greater than 0.6.

[0119] (Example 2) This example describes an evaluation of the output characteristics of a secondary battery. A coating layer is formed on the surface of the positive electrode active materials used in this example (Table 3, active materials D1, D3, E1-E3). The manufacturing method of active materials D1, D3, E1-E3 and the evaluation method of their output characteristics are as follows.

[0120] [Method for preparing active materials D1, D3, and E1-E3] A coating layer was formed on the surfaces of the active materials A1, A3, and C1-C3 obtained in Example 1 by the following method. First, 4.52 g of metaphosphoric acid was dissolved in 191.8 g of deionized water. Boric acid was dissolved in this solution, and boron was added to the solution in a molar ratio of 1.0 to phosphorus. Then, lithium hydroxide monohydrate was dissolved in this solution, and lithium was added to the solution in a molar ratio of 1.0 to the total amount of phosphorus and boron. A coating solution was obtained as a result.

[0121] Next, a slurry mixture was prepared by mixing the coating solution with one of the active materials A1, A3, or C1-C3. This mixture was dried by spray drying and then heated in an air atmosphere at 200°C for 5 hours. As a result, a coating layer containing Li, B, P, and O was formed on the surface of the positive electrode active material.

[0122] Next, the positive electrode active material was doped with Li using the following method. First, 9-fluorenone was mixed with tetrahydrofuran in a glove box under an argon atmosphere to obtain a fluorenone solution. After adding Li foil to this fluorenone solution, it was stirred for 2 hours to obtain a reducing solution containing Li ions. Then, the positive electrode active material was added to the reducing solution and stirred for 24 hours. After stirring was complete, the positive electrode active material was washed with tetrahydrofuran and then filtered off by vacuum filtration. This positive electrode active material was heated overnight at 120°C to dry it. By doing so, the positive electrode active material was doped with Li to obtain the active materials D1, D3, and E1-E3 shown in Table 3.

[0123] [Configuration and manufacturing method of secondary battery for evaluation] • Method for manufacturing the positive electrode Active materials D1, D3, and E1-E3, sulfide solid electrolyte, vapor-deposited carbon fiber (VGCF), and styrene-butadiene rubber binder were weighed in a mass ratio of active material:sulfide solid electrolyte:VGCF:binder = 81:16:1:2. The weighed components were mixed with diisobutyl ketone (DIBK) and dispersed in the DIBK to prepare a cathode composite material.

[0124] This positive electrode composite was coated onto an Al foil, which served as the positive electrode current collector foil, using a blade method. Subsequently, the positive electrode current collector foil was heated on a hot plate to dry the positive electrode composite, thereby forming a positive electrode active material layer on the foil. The positive electrode was thus obtained.

[0125] • Method for manufacturing the negative electrode Lithium titanate (LTO) as the negative electrode active material, sulfide solid electrolyte, VGCF, and polyvinylidene fluoride (PVdF)-based binder were weighed in a mass ratio of negative electrode active material:sulfide solid electrolyte:VGCF:binder = 72:23:3:2. The weighed components were mixed with butyl butyrate and dispersed in the butyl butyrate to prepare the negative electrode composite material.

[0126] This negative electrode composite was coated onto a Ni foil serving as the negative electrode current collector foil using a blade method. Subsequently, the negative electrode current collector foil was heated on a hot plate to dry the negative electrode composite, thereby forming a negative electrode active material layer on the negative electrode current collector foil. The negative electrode was thus obtained.

[0127] • Method for preparing a solid electrolyte layer The sulfide solid electrolyte and PVdF-based binder were weighed in a mass ratio of sulfide solid electrolyte:binder = 99.4:0.6. Each weighed component was mixed with butyl butyrate and stirred using an ultrasonic dispersion device to obtain a solid electrolyte mixture. This solid electrolyte mixture was coated onto an aluminum foil substrate using the blade method. Subsequently, the substrate was heated on a hot plate to dry the solid electrolyte mixture, thereby forming a solid electrolyte layer on the substrate.

[0128] • Assembly of evaluation rechargeable batteries The positive electrode and the substrate were stacked so that the positive electrode active material layer and the solid electrolyte layer were in contact. This laminate was pressed using a roll press machine at a press pressure of 50 kN / cm and a temperature of 160°C to tightly bond the positive electrode active material layer and the solid electrolyte layer. After peeling the substrate from the pressed laminate, 1 cm 2 A positive electrode laminate was obtained by punching out the material to the specified size.

[0129] Furthermore, the negative electrode and the substrate were stacked so that the negative electrode active material layer and the solid electrolyte layer were in contact. This laminate was pressed using a roll press machine at a press pressure of 50 kN / cm and a temperature of 160°C to ensure close contact between the negative electrode active material layer and the solid electrolyte layer. After the pressing was completed, the substrate was peeled off the laminate.

[0130] Next, the laminate and the substrate were stacked so that the solid electrolyte layers were in contact with each other. This laminate was then pre-pressed using a flat single-axis press at a press pressure of 100 MPa and a temperature of 25°C to ensure that the solid electrolyte layers were tightly bonded together. After peeling the substrate from the pressed laminate, 1.08 cm 2 The negative electrode laminate was obtained by punching out the material to the specified size.

[0131] The positive electrode laminate and negative electrode laminate obtained as described above were stacked so that their solid electrolyte layers were in contact with each other. This laminate was then pressed using a flat-axis press at a pressure of 200 MPa and a temperature of 120°C to tightly bond the solid electrolyte layers together. A battery laminate was thus obtained.

[0132] The resulting battery stack was then sandwiched between two restraining plates, and a pressure of 5 MPa was applied between the restraining plates using fasteners. This completed the process to obtain a secondary battery for evaluation.

[0133] [Evaluation of output characteristics] The output characteristics were evaluated using the secondary battery obtained as described above. A charge / discharge device (Bio-Logic's "BCS-815") was used for the evaluation of the output characteristics. The evaluation of the output characteristics was performed in a constant temperature chamber maintained at 25°C.

[0134] To evaluate the output characteristics, the evaluation secondary battery was first charged from 0.45V to 3.25V at a current density equivalent to 0.1C. Then, the battery was discharged until the charge level (i.e., State of Charge) reached 50%. After reaching 50% charge, it was discharged for 10 seconds at a current density equivalent to 3.0C. The 0.1s resistance was calculated by dividing the potential at 0.1 seconds after the start of discharge by the discharge current. Similarly, the 10s resistance was calculated by dividing the potential at 10 seconds after the start of discharge by the discharge current.

[0135] The unit "C" for current density during charging and discharging theoretically represents the current density at which the charge or discharge rate reaches 100% in one hour. In other words, theoretically, a secondary battery can be completely discharged by discharging at a current density of 1C for one hour. In this example, the current density equivalent to 1C is specifically 220mA / g. The 0.1s resistance and 10s resistance for each active material are shown in Table 3.

[0136] [Table 3]

[0137] As shown in Table 3, batteries using active materials D1 and D3 had lower 0.1s and 10s resistances than batteries using active materials E1 to E3. From these results, it can be understood that the internal resistance of a battery can be reduced by using a positive electrode active material composed of active material particles having the specific composition and crystal structure, and whose aspect ratio standard deviation is within the specific range.

[0138] As described above, the embodiments of the positive electrode active material, the method for producing the same, and the non-aqueous electrolyte secondary battery have been explained based on Examples 1 to 2, but the specific aspects of the positive electrode active material, the method for producing the same, and the non-aqueous electrolyte secondary battery according to the present invention are not limited to the aspects of the Examples, and the configuration can be appropriately modified within a range that does not impair the gist of the present invention.

[0139] For example, the positive electrode active material can adopt the aspects according to the following [1] to [3].

[0140] [1] A positive electrode active material for use in a non-aqueous electrolyte secondary battery, wherein the active material particles constituting the positive electrode active material are represented by a composition formula of Li a Na b Ni c Co d Mn e Nb f M g O2 (provided that a to g in the composition formula satisfy the relationships of 0.6<a≦1.4, 0≦b≦0.2, 0.1<c<0.3, 0<d<0.65, 0.3<e<0.9, 0.005<f<0.1, and 0≦g<0.2, and M is at least one additive element selected from the group consisting of B, Mg, Al, K, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Mo, and W), and has an O2-type layered structure assignable to space group P63mc, and has an O2-type layered structure assignable to space group P63mc, wherein when the Feret diameter in the c-axis direction in the secondary electron image of each individual active material particle is represented as L C (unit: μm), and the Feret diameter in the direction perpendicular to the c-axis is represented as L A (unit: μm), the standard deviation of the aspect ratio A represented by the following formula (1) is 0.6 or less. A=L A / L C ···(1)

[0141] [2] The positive electrode active material according to [1], wherein the arithmetic mean value of the aspect ratio A is 0.8 or more and 1.5 or less. 〔3〕The active material particle has a surface layer portion covering the outermost surface thereof, and the Nb concentration in the surface layer portion is higher than the average concentration of Nb contained in the active material particle, the positive electrode active material according to〔1〕or〔2〕.

[0142] The non-aqueous electrolyte secondary battery can adopt, for example, an aspect according to the following〔4〕. 〔4〕A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte, wherein The positive electrode comprises the positive electrode active material according to any one of〔1〕to〔3〕, the non-aqueous electrolyte secondary battery.

[0143] The method for producing the positive electrode active material can adopt aspects according to the following〔5〕to〔6〕. 〔5〕The method for producing the positive electrode active material according to any one of〔1〕to〔3〕, wherein A precursor containing two or more elements selected from the group consisting of Ni, Co, Mn, Nb and the aforementioned additive element M is produced, A mixture comprising the aforementioned precursor, a Na source and a Nb source is fired in an oxidizing gas atmosphere, thereby producing Na b0 Ni c Co d Mn e Nb f M g A Na-doped precursor having a composition represented by the compositional formula O2 (provided that b0 to g in the aforementioned compositional formula satisfy the relationships 0.6<b0≦1.6, 0.1<c<0.3, 0<d<0.65, 0.3<e<0.9, 0.005<f<0.1, 0≦g<0.2, and M is at least one additive element selected from the group consisting of B, Mg, Al, K, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Mo and W.) and having a P2-type layered structure is produced, A mixture of the aforementioned Na-doped precursor and a Li source is heated, and Na in the aforementioned Na-doped precursor is substituted with Li by ion exchange, thereby producing the positive electrode active material, the method for producing the positive electrode active material.

[0144] [6] The method for producing a positive electrode active material according to [5], wherein the Nb source is at least one Nb-containing compound selected from the group consisting of ammonium niobium oxalate, niobethoxide, niobium pentoxide, niobium hydroxide, and niobium pentachloride. [Explanation of symbols]

[0145] 1 Cathode active material 10 Active material particles 103 Ridge

Claims

1. A positive electrode active material used in non-aqueous electrolyte secondary batteries, The active material particles constituting the positive electrode active material are Li a Na b Ni c Co d Mn e Nb f M g O 2 The composition is represented by the compositional formula (wherein a to g in the compositional formula satisfy the relationships 0.6 < a ≤ 1.4, 0 ≤ b ≤ 0.2, 0.1 < c < 0.3, 0 < d < 0.65, 0.3 < e < 0.9, 0.005 < f < 0.1, 0 ≤ g < 0.2, and M is at least one additive element selected from the group consisting of B, Mg, Al, K, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Mo, and W), Space group P6 3 and an O2-type layered structure assignable to mc, The c-axis direction of the Ferret diameter in the secondary electron image of each of the active material particles is L. C Expressed as (unit: μm), the Ferret diameter in the direction perpendicular to the c-axis is L A A positive electrode active material in which the standard deviation of the aspect ratio A, expressed by the following formula (1) (in units of μm), is 0.6 or less. A=L A / L C ・・・(1)

2. The positive electrode active material according to claim 1, wherein the arithmetic mean of the aspect ratio A is 0.8 or more and 1.5 or less.

3. The positive electrode active material according to claim 1, wherein the active material particles have a surface layer covering their outermost surface, and the Nb concentration of the surface layer is higher than the average concentration of Nb contained in the active material particles.

4. A non-aqueous electrolyte secondary battery having a positive electrode, a negative electrode, and a non-aqueous electrolyte, The positive electrode comprises the positive electrode active material described in any one of claims 1 to 3, in a non-aqueous electrolyte secondary battery.

5. A method for producing a positive electrode active material according to any one of claims 1 to 3, A precursor is prepared containing two or more elements selected from the group consisting of Ni, Co, Mn, Nb, and the aforementioned additive element M. By calcining a mixture containing the aforementioned precursor, a Na source, and an Nb source in an oxidizing gas atmosphere, Na b0 Ni c Co d Mn e Nb f M g O 2 A Na-doped precursor having a composition represented by the composition formula (wherein b0 to g in the composition formula satisfy the relationships 0.6 < b0 ≤ 1.6, 0.1 < c < 0.3, 0 < d < 0.65, 0.3 < e < 0.9, 0.005 < f < 0.1, 0 ≤ g < 0.2, and M is at least one additive element selected from the group consisting of B, Mg, Al, K, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Mo, and W) and a P2-type layered structure is prepared. A method for producing a positive electrode active material, comprising heating a mixture of the Na-doped precursor and a Li source, and replacing the Na in the Na-doped precursor with Li by ion exchange.

6. The method for producing a positive electrode active material according to claim 5, wherein the Nb source is at least one Nb-containing compound selected from the group consisting of ammonium niobium oxalate, niobethoxide, niobium pentoxide, niobium hydroxide, and niobium pentachloride.

Citation Information

Patent Citations

  • Method for producing positive electrode active material and method for manufacturing lithium ion battery

    JP2021068555A